Endovascular Treatment with Limus Eluting Stents in Patients with Acute Coronary Syndrome - M. V. Chernyayev; A. G. Faybushevich; Y. S. Muzganova (Неотложная медицинская помощь)
BACKGROUND Coronary heart disease is one of the main causes of the population’s disability and mortality in Russia and abroad. Revascularization with coronary stents in the course of the most suitable drug therapy is one of the most important treatments of coronary heart disease. It is essential to pay special attention to the research results of using modern stents, in particular, the frst Russian drug-eluting stent “CALYPSO”.AIM OF STUDY To study immediate and medium-term results of Limus-eluting stents procedure in patients with acute coronary syndrome.MATERIAL AND METHODS 304 patients with acute coronary syndrome were included into the research and were divided into 2 groups. The frst group consisted of 156 patients with CALYPSO stent (Angioline, Russia). The other group consisted of 148 patients who had undergone revascularization with the XIENCE stent (Abbot Vascular, USA). Their health state was monitored via phone 3, 6, 9 and 12 months later. After the discharge from the hospital, the drug therapy was prescribed, and instrumental procedures of diagnostics were planned for the period of 9–12 months. According to the results of the examination, patients with suspected or confrmed myocardial ischemia underwent follow-up coronary angiography.RESULTS The success of implantation was 98.63% in the frst group, and 99.4% in the second group. One fatal outcome occurred in both groups during hospitalization (thus making 0.64% и 0.67%). The placement of the CALYPSO stent in distal parts of coronary arteries requested signifcantly less time and contrast. Medium-term results of stenting in both groups appeared to be comparable (thus, all cause death 3 (1.92%) and 2 (1.35%), restenosis >50% 3 (1.92%) and 3 (2 %), late thrombosis — 0 in both groups, cardiac death — 0 in both groups. End points (MACE) in both groups were 1.28% and 0.67%.CONCLUSION Taking into consideration immediate and medium-term results it can be concluded that domestic stents (CALYPSO) are comparable to stents XIENCE. The CALYPSO stent is more advantageous than the XIENCE in the delivery to the lesion focus while performing the procedure in distal ﬂow.